Composite material for 3D printing and preparation method thereof
By mixing grains and squeezing into wires and squeezing into cable by mixeding with polystramlifxyl -dimly glycolin, anti -rushing agent, tea residue, and calcium carbonate, the existing 3D printing materials have poor mechanical performance and high cost The problem realizes high -performance, low -cost composite 3D printing materials.
Patent Information
- Application Number
- CN202411660531.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
AI Technical Summary
Existing composite materials for 3D printing have shortcomings in terms of mechanical properties and costs, especially polylactic acid (PLA) materials are brittle and costly, which cannot meet the long-term development needs of enterprises.
Composite materials such as polystrackic acid, polytexyl diicate, anti -rushing agent, tea residue, and calcium carbonate are composite. The process of becoming a wires prepares a composite 3D printing wire with compatibility.
In the case of not being chemically treated with tea residue, improve the compatibility between the tea residue and the clustering of the polymapilic acid, reduce the cost, and reduce the production of waste liquid. At the same time, the smell and color of the tea residue are preserved. Printing performance and mechanical performance.
Smart Images

Figure BDA0005143214350000071 
Figure BDA0005143214350000081 
Figure BDA0005143214350000082
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing, and in particular to a composite material for 3D printing and a preparation method thereof. Background Art
[0002] At present, additive manufacturing is leading the world through an important industrial revolution as one of the main driving forces. Additive manufacturing, also known as "3D printing", integrates many cutting-edge technologies such as materials science, electrical control technology, digital technology, information science and technology. Compared with traditional manufacturing methods such as injection molding and casting, 3D printing has the advantages of high-precision manufacturing of complex structures, saving materials and time, high design freedom and personalized customization. It constantly breaks through the limits of product design, manufacturing and use, and brings new development opportunities to traditional manufacturing. Among them, fused deposition modeling (FDM) technology is a method that does not rely on lasers, but heats and melts various thermoplastic plastic wires to form them. Its easy operation and high cost-effectiveness make it widely used in the civilian field.
[0003] The more common FDM 3D printing polymer materials on the market are: PLA, ABS, PETG, PC, PEEK, etc. Among them, polylactic acid (PLA) is the most commonly used 3D printing material. Its advantage is that it has no unpleasant odor when melted, and it is derived from biomass raw materials such as corn and can be completely degraded. However, it also has disadvantages such as poor mechanical properties and easy brittle fracture, which greatly limits the performance and application of printed objects, has high cost, and cannot meet the needs of long-term development and use of enterprises;
[0004] In view of the above situation, it is necessary to improve the existing composite materials used for 3D printing so that they can adapt to the current needs for the use of 3D printing materials. Summary of the invention
[0005] To solve the above technical problems, the present invention provides a composite material for 3D printing, which is composed of the following raw materials in parts by weight: 60-80 parts of polylactic acid, 5-20 parts of polybutylene succinate, 3-15 parts of impact modifier, 5-15 parts of tea residues, and 5-15 parts of calcium carbonate.
[0006] As a further supplement to the technical solution, the amount of the polylactic acid is 70 parts.
[0007] As a further supplement to the technical solution, the amount of polybutylene succinate is 8 parts.
[0008] As a further supplement to the technical solution, the impact modifier is an olefin copolymer impact modifier, and the impact modifier is 6 parts.
[0009] As a further supplement to the technical solution, the particle size of the tea residue is 400-1000 mesh, and the tea residue is 10 parts.
[0010] To further supplement the technical solution, the amount of calcium carbonate is 6 parts.
[0011] A method for preparing a composite material for 3D printing comprises the following steps:
[0012] Step 1: Evenly mix polylactic acid, polybutylene succinate, impact modifier, tea residue and calcium carbonate to make each component completely dispersed;
[0013] Step 2: The mixture is blended and granulated by a twin-screw extruder at a blending temperature of 150-200°C;
[0014] Step 3: drying the blended particles in a drying oven at a temperature of 50-100°C for a drying time of 6-12 hours;
[0015] Step 4: Extruding the dried particles into wires through a single screw extruder at 150-190°C, and rolling them up to obtain composite 3D printing wires;
[0016] Step 5: The filament dried in step 4 is tested for printing performance and mechanical properties by a 3D printer. The printing temperature is 180℃-230℃, the printing speed is 50-200mm / s, and the base plate temperature does not need to be set.
[0017] As a further supplement to the technical solution, the blending temperature of the twin-screw extruder is 160-190°C.
[0018] As a further supplement to the technical solution, the drying temperature is 80-100°C.
[0019] As a further supplement to the technical solution, the single screw extrusion temperature is 160-180°C.
[0020] The beneficial effect is that the present invention adopts tea residues of finer size, and utilizes impact modifier and polybutylene succinate to synergistically improve the compatibility between tea residues and polylactic acid matrix, while the prior art often requires pre-activation treatment of tea residues, which is a cumbersome process and produces more waste liquid and high cost. The present invention does not need to modify the tea residues, but only needs to control the particle size and uniformity thereof. The prepared composite material still has similar properties to the composite material prepared by modified tea residues, and its appearance has more characteristics and smell of tea residues. DETAILED DESCRIPTION
[0021] In order to make the technical solution more clear to those skilled in the art, the technical solution of the present invention will be described in detail below:
[0022] A composite material for 3D printing, comprising the following steps:
[0023] Step 1: Evenly mix polylactic acid (PLA), polybutylene succinate (PBS), impact modifier, tea residue and calcium carbonate to make each component completely dispersed;
[0024] Step 2: The mixture is blended and granulated by a twin-screw extruder at a blending temperature of 150-200°C;
[0025] Step 3: drying the blended particles in a drying oven at a temperature of 50-100°C for a drying time of 6-12 hours;
[0026] Step 4: Extruding the dried particles into wires through a single screw extruder at 150-190°C, and rolling them up to obtain PLA / tea residue composite 3D printing wires;
[0027] Step 5: The filament dried in step 4 is tested for printing performance and mechanical properties by a 3D printer. The printing temperature is 180℃-230℃, the printing speed is 50-200mm / s, and the base plate temperature does not need to be set.
[0028] Among them, the amount of PLA added is preferably 60-80 parts, more preferably 70 parts.
[0029] The amount of PBS added is preferably 5-20 parts, more preferably 8 parts.
[0030] Among them, the impact modifier is preferably an olefin copolymer impact modifier, such as EBA, GMA, etc., and the added amount is preferably 3-15 parts, more preferably 6 parts.
[0031] Among them, the particle size of tea residue is preferably 400-1000 mesh, more preferably 600 mesh, and the added amount is preferably 5-15 parts, more preferably 10 parts.
[0032] Among them, the addition amount of calcium carbonate is preferably 5-15 parts, more preferably 6 parts.
[0033] The blending temperature of the twin-screw extruder is preferably 160-190°C, more preferably 180°C.
[0034] Among them, the drying temperature is preferably 80-100°C, and the drying time is preferably 8h.
[0035] The single screw extrusion temperature is preferably 160-180°C, more preferably 180°C.
[0036] Example 1
[0037] A composite material for 3D printing, comprising the following steps:
[0038] Step 1: Weigh the dried PLA, PBS, EBA impact modifier, tea residue, and calcium carbonate in a ratio of 70 / 10 / 5 / 10 / 5 and mix them in a high-speed mixer;
[0039] Step 2: After the particles in step 1 are evenly mixed, they are granulated by a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are set to 130°C, 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C;
[0040] Step 3: Place the granules prepared in step 2 in a drying oven at 80-100°C and dry for 8 hours;
[0041] Step 4: extrude the dried material in step 3 into a single screw extruder, the temperature of each zone of the extruder is 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, and cooled by a water cooling tank and an air cooling machine to prepare a wire with a diameter of 1.75 mm, and then coiled by a coiling machine, dried, and finally sealed for storage;
[0042] Step 5: The filament dried in step 4 is tested for printing performance and mechanical properties by a 3D printer. The printing temperature is 180℃-230℃, the printing speed is 50-200mm / s, and the base plate temperature does not need to be set.
[0043] Example 2
[0044] A composite material for 3D printing, comprising the following steps:
[0045] Step 1: Weigh the dried PLA, PBS, GMA impact modifier, tea residue, and calcium carbonate in a ratio of 70 / 5 / 10 / 10 / 5 and mix them in a high-speed mixer;
[0046] Step 2: After the particles in step 1 are evenly mixed, they are granulated by a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are set to 130°C, 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C;
[0047] Step 3: Place the granules prepared in step 2 in a drying oven at 80-100°C and dry for 8 hours;
[0048] Step 4: extrude the dried material in step 3 into a single screw extruder, the temperature of each zone of the extruder is 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, and cooled by a water cooling tank and an air cooling machine to prepare a wire with a diameter of 1.75 mm, and then coiled by a coiling machine, dried, and finally sealed for storage;
[0049] Step 5: The filament dried in step 4 is tested for printing performance and mechanical properties by a 3D printer. The printing temperature is 180℃-230℃, the printing speed is 50-200mm / s, and the base plate temperature does not need to be set.
[0050] Example 3
[0051] A composite material for 3D printing, comprising the following steps:
[0052] Step 1: Weigh the dried PLA, PBS, EBA impact modifier, GMA impact modifier, tea residue, and calcium carbonate in a ratio of 70 / 5 / 5 / 5 / 10 / 5, and mix them in a high-speed mixer;
[0053] Step 2: After the particles in step 1 are evenly mixed, they are granulated by a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are set to 130°C, 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C;
[0054] Step 3: Place the granules prepared in step 2 in a drying oven at 80-100°C and dry for 8 hours;
[0055] Step 4: extrude the dried material in step 3 into a single screw extruder, the temperature of each zone of the extruder is 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, and cooled by a water cooling tank and an air cooling machine to prepare a wire with a diameter of 1.75 mm, and then coiled by a coiling machine, dried, and finally sealed for storage;
[0056] Step 5: The filament dried in step 4 is tested for printing performance and mechanical properties by a 3D printer. The printing temperature is 180℃-230℃, the printing speed is 50-200mm / s, and the base plate temperature does not need to be set.
[0057] Example 4
[0058] A composite material for 3D printing, comprising the following steps:
[0059] Step 1: Weigh the dried PLA, PBS, EBA impact modifier tea dregs, and calcium carbonate in a ratio of 70 / 5 / 5 / 15 / 5 and mix them in a high-speed mixer;
[0060] Step 2: After the particles in step 1 are evenly mixed, they are granulated by a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are set to 130°C, 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C;
[0061] Step 3: Place the granules prepared in step 2 in a drying oven at 80-100°C and dry for 8 hours;
[0062] Step 4: extrude the dried material in step 3 into a single screw extruder, the temperature of each zone of the extruder is 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, and cooled by a water cooling tank and an air cooling machine to prepare a wire with a diameter of 1.75 mm, and then coiled by a coiling machine, dried, and finally sealed for storage;
[0063] Step 5: The filament dried in step 4 is tested for printing performance and mechanical properties by a 3D printer. The printing temperature is 180℃-230℃, the printing speed is 50-200mm / s, and the base plate temperature does not need to be set.
[0064] Example 5
[0065] A composite material for 3D printing, comprising the following steps:
[0066] Step 1: Weigh the dried PLA, PBS, GMA impact modifier, tea residue, and calcium carbonate in a ratio of 70 / 5 / 5 / 15 / 5 and mix them in a high-speed mixer;
[0067] Step 2: After the particles in step 1 are evenly mixed, they are granulated by a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are set to 130°C, 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C;
[0068] Step 3: Place the granules prepared in step 2 in a drying oven at 80-100°C and dry for 8 hours;
[0069] Step 4: extrude the dried material in step 3 into a single screw extruder, the temperature of each zone of the extruder is 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, and cooled by a water cooling tank and an air cooling machine to prepare a wire with a diameter of 1.75 mm, and then coiled by a coiling machine, dried, and finally sealed for storage;
[0070] Step 5: The filament dried in step 4 is tested for printing performance and mechanical properties by a 3D printer. The printing temperature is 180℃-230℃, the printing speed is 50-200mm / s, and the base plate temperature does not need to be set.
[0071] Example 6
[0072] A composite material for 3D printing, comprising the following steps:
[0073] Step 1: Weigh the dried PLA, PBS, EBA impact modifier, GMA impact modifier, tea residue, and calcium carbonate in a ratio of 70 / 5 / 2.5 / 2.5 / 15 / 5 and mix them in a high-speed mixer;
[0074] Step 2: After the particles in step 1 are evenly mixed, they are granulated by a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are set to 130°C, 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C;
[0075] Step 3: Place the granules prepared in step 2 in a drying oven at 80-100°C and dry for 8 hours;
[0076] Step 4: extrude the dried material in step 3 into a single screw extruder, the temperature of each zone of the extruder is 150°C, 170°C, 180°C, 180°C, 180°C, 180°C, and cooled by a water cooling tank and an air cooling machine to prepare a wire with a diameter of 1.75 mm, and then coiled by a coiling machine, dried, and finally sealed for storage;
[0077] Step 5: The filament dried in step 4 is tested for printing performance and mechanical properties by a 3D printer. The printing temperature is 180℃-230℃, the printing speed is 50-200mm / s, and the base plate temperature does not need to be set.
[0078] Comparative Example 1
[0079] A PLA / tea residue composite material, which is different from Example 2 in that no impact modifier is added, the size of the tea residue is 200 mesh, and other raw materials and preparation process remain unchanged.
[0080] Comparative Example 2
[0081] A PLA / tea residue composite material, which is different from Example 2 in that no impact modifier is added, the size of the tea residue is 100 mesh, and other raw materials and preparation process remain unchanged.
[0082] Comparative Example 3
[0083] A PLA / tea residue composite material, which is different from Example 2 in that calcium carbonate is not added, the size of the tea residue is 200 mesh, and other raw materials and preparation process remain unchanged.
[0084] Comparative Example 4
[0085] A PLA / tea residue composite material, which is different from Example 2 in that calcium carbonate is not added, the size of the tea residue is 100 mesh, and other raw materials and preparation process remain unchanged.
[0086] Table 1 below shows the performance indicators of Examples 1-5;
[0087] Table 1
[0088]
[0089]
[0090] Table 2 below shows the performance indicators of Comparative Examples 1-4:
[0091] Table 2
[0092]
[0093]
[0094] While preparing the PLA / tea dregs 3D printing composite material, without the need for chemical treatment of the tea dregs, it not only saves costs and reduces the generation of waste liquid, retains the smell and color of the tea dregs themselves, but also better avoids the problem of poor compatibility between PLA and tea dregs. The resulting filament has excellent printing performance and outstanding mechanical properties, and the printed products retain the original smell, texture and color of the tea dregs to a great extent.
[0095] Among them, in the present application, the PLA / tea residue composite material may have problems such as tea residue agglomeration during pre-mixing during the granulation process, resulting in ineffective and uniform dispersion, which leads to difficulties in granulation. There is a solution to this phenomenon, that is, first pre-mix other raw materials except tea residue with diffusion oil, and then add tea residue for mixing, which can make the tea residue dispersed evenly to the greatest extent. If this formula has some problems with printing fluidity, there is also an alternative solution, that is, replace the calcium carbonate in the formula with glass microspheres, and the added amount is the same as the calcium carbonate content. The formula changed to glass microspheres can have the same printing performance and mechanical properties, and the fluidity is better.
[0096] The above technical solutions only reflect the preferred technical solutions of the technical solutions of the present invention. Some changes that may be made to certain parts thereof by technicians in this technical field all reflect the principles of the present invention and fall within the protection scope of the present invention.
Claims
1. A composite material for 3D printing, characterized in that: The invention is composed of the following raw materials in parts by weight: 60-80 parts of polylactic acid, 5-20 parts of polybutylene succinate, 3-15 parts of impact modifier, 5-15 parts of tea residue and 5-15 parts of calcium carbonate.
2. A composite material for 3D printing according to claim 1, characterized in that: The polylactic acid is 70 parts.
3. A composite material for 3D printing according to claim 2, characterized in that: The polybutylene succinate is 8 parts.
4. The composite material for 3D printing according to claim 3, characterized in that: The impact modifier is an olefin copolymer impact modifier, and the impact modifier is 6 parts.
5. The composite material for 3D printing according to claim 4, characterized in that: The particle size of the tea residue is selected to be 400-1000 mesh, and the tea residue is 10 parts.
6. The composite material for 3D printing according to claim 5, characterized in that: The calcium carbonate is 6 parts.
7. A method for preparing a composite material for 3D printing according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Evenly mix polylactic acid, polybutylene succinate, impact modifier, tea residue and calcium carbonate to make each component completely dispersed; Step 2: The mixture is blended and granulated by a twin-screw extruder at a blending temperature of 150-200°C; Step 3: drying the blended particles in a drying oven at a temperature of 50-100°C for a drying time of 6-12 hours; Step 4: Extruding the dried particles into wires through a single screw extruder at 150-190°C, and rolling them up to obtain composite 3D printing wires; Step 5: The filament dried in step 4 is tested for printing performance and mechanical properties by a 3D printer. The printing temperature is 180℃-230℃, the printing speed is 50-200mm / s, and the base plate temperature does not need to be set.
8. The method for preparing a composite material for 3D printing according to claim 7, characterized in that: The twin-screw extruder blending temperature is 160-190°C.
9. The method for preparing a composite material for 3D printing according to claim 7, characterized in that: The drying temperature is 80-100°C.
10. The method for preparing a composite material for 3D printing according to claim 7, characterized in that: The single screw extrusion temperature is 160-180°C.